ELECTRODEPOSITION OF Cu ON THE SURFACE OF SILICA FREE RICE HUSK ACTIVATED CARBON WITH ULTRASONIC IRRADIATION - Ryan Andhika; Muhammad Zakir; Maming Maming (Hasanuddin University, 2015)
Electrodeposition of Cu on the surface of silica free rice husk activated carbon with ultrasonic irradiation aimed to increase the value of specific capacitance was carried out. Silica free rice husk activated carbon was synthesized using H3PO4 activator and extraction of silica using KOH. The surface area of rice husk carbon was obtained before and after the extraction of silica and after activation were 57.2833 m2/g, 180.5378 m2/g and 184.6074 m2/g, respectively. XRF analysis showed that Cu depositioned on the surface of silica free rice husk activated carbon and based of CV measurements showed that electrodeposition of Cu with ultrasonic irradiation can increased the value of specific capacitance. Specific capacitance of silica free rice husk activated carbon before and after electrodeposition of Cu with ultrasonic irradiation were 657.75 nF/g and 721.08 nF/g, respectively.